The demand side of social protection: Lessons from Cambodia's labour rights experience - Alisa DiCaprio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
In fragile states, social protection programmes are often a kaleidoscope of projects financed and implemented by a variety of donors, government agencies and NGOs. Such an environment does not foster a strong sense of ownership by beneficiaries, which weakens the likelihood of sustainability in the absence of donor interest or government commitment. Loosening demand-side constraints may provide incentive to sustain social progress, but it is unclear what political or social structures can effectively facilitate voice in fragile states. Cambodia's unusual social protection trajectory offers some insight by presenting an example where labour rights has made substantial progress while all other protections lag. We assess whether the changed external environment might facilitate activism in other areas of social protection. Our analysis suggests that using an island of excellence to build institutions that open political space for activism can be a successful strategy in states where governments are unable or unwilling to provide comprehensive social protection systems.
Keywords: J51; J83; J88; K31; 330; fragile states; Asia; social protection; Cambodia; social movements; labour standards; Soziale Sicherung; Arbeitsrecht; Soziale Bewegung; Kambodscha